Raising Legal Awareness on the Importance of Trademark Registration for Household Product Protection - Hasima, Rahman; Tatawu, Guasman; Sulihin, La Ode Muhamad; Isnayanti, Isnayanti (DAS SEIN: Jurnal Pengabdian Hukum dan Humaniora (Journal of Legal Services and Humanities), 2025)
This writing aims to enhance the legal awareness of home industry actors in Tombawatu Village, Konawe Regency, regarding the importance of trademark registration for legal protection and certainty. Despite being a tourism area with many home industry businesses, the awareness of trademark registration among entrepreneurs remains low. The objectives of this community service activity were to improve the understanding of business actors about trademark registration and its legal benefits. The methodology employed in this study involved several stages. The first stage was the preparation phase, which included a location survey and determining the target audience. The second stage was the implementation phase, which consisted of a pre-test, delivery of material through lectures and discussions, followed by a post-test to assess the level of understanding of the participants. The community service activities used a lecture and discussion method conducted through direct face-to-face interaction with the community. The results showed a significant improvement in legal awareness among the participants regarding trademark registration and its procedures. Before the legal counseling, 80% of the participants had low legal awareness. After the counseling session, 60% of participants demonstrated a high level of understanding, while 20% showed a very high level of understanding, and none had a low level of understanding. This indicates a successful increase in legal awareness and understanding of trademark registration among the home industry entrepreneurs in Tombawatu Village.